Visual Outcomes After Pars Plana Vitrectomy in Fresh versus Longstanding Rhegmatogenous Retinal Detachment: A Prospective Observational Study - Alam, Md Mahfuzul; Roy, Pankaj Kumar; Hasan, Md Zahidul; Kamal, Abu Mohammad Mostofa; Mozid, Abeed; Naim, Tajkiratun (Journal of National Institute of Ophthalmology, 2026)
Background: Rhegmatogenous retinal detachment (RRD) is a vision-threatening condition requiring urgent surgical intervention. The timing of surgery may influence postoperative visual outcomes. Objective: To compare visual outcomes after pars plana vitrectomy (PPV) in fresh RRD (<3 months duration) and longstanding RRD (>3 months duration) cases. Methods: A prospective observational study was conducted at the National Institute of Ophthalmology and Hospital, Dhaka (June 2022–May 2023). Ninety patients aged 20–75 years with RRD were enrolled and divided into Group I (fresh RRD, n=50) and Group II (longstanding RRD with proliferative vitreoretinopathy ≤ grade B, n=40). All underwent PPV with silicone oil tamponade. Best-corrected visual acuity (BCVA) was measured preoperatively and at 45 days postoperatively, converted to logMAR for analysis. Statistical tests included chi-square and unpaired t-test; p<0.05 was considered significant. Results: The mean preoperative BCVA was 1.4 ± 0.6 logMAR in fresh RRD and 2.4 ± 0.6 logMAR in longstanding RRD (p<0.001). At 45 days, mean BCVA improved to 0.7 ± 0.5 in fresh RRD versus 1.7 ± 0.4 in longstanding RRD (p<0.001). Anatomical success (retinal reattachment) was comparable between groups (fresh: 88.9%, longstanding: 86.1%). Conclusion: PPV in fresh RRD yields significantly better postoperative visual outcomes than in longstanding RRD, despite similar anatomical success rates. Early surgical intervention is critical to optimizing visual recovery. J.Natl.Inst.Ophthalmol.2024;7(1): 35-40